Candidate Entry, Screening, and the Political Budget Cycle - Le Borgne, Eric.; Lockwood, Ben. (Washington, D.C. : International Monetary Fund, 2002)
We investigate whether private information about citizens' competence in political office can be revealed by their entry and campaign expenditure decisions. We find that this depends on whether voters and candidates have common or conflicting interests; only in the former case can entry be revealing. We apply these results to Rogoff's (1990) political budget cycle model: as interests are common, low-ability candidates are screened out at the entry stage, and so there is no signaling via fiscal policy. In a variant of Rogoff's model where citizens differ in honesty, interests are conflicting, so the political budget cycle can persist.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet